Análisis molecular de la cascada genética de sonic hedgehog en el desarrollo de los arcos branquiales en Xenopus laevis - Pacheco Silva, Grazielle (2015)
The generation of the craniofacial complex is a process that requires considerable organization. The vertebrate head is a composite structure whose formation begins early in development, when the brain starts to form. Cells of the neural crest have a fundamental importance in this process. The neural crest constitutes a multipotent cell population, which gives rise to a broad range of derivatives, including pigment cells, craniofacial skeleton, connective tissues, neurons and glia of the peripheral nervous system. In Xenopus, three major populations of migrating cranial neural crest cells originate at distinct axial levels of the mid- and hindbrain and target the first mandibular arch, the second hyoid arch and the third and fourth branchial arches.\nSonic hedgehog overexpression leads to an enlargement of the visceral and branchial arches. Conversely, knocking down Shh shows a complete disorganization of the arches, leading to an alteration in the formation of the face. These results indicate that Shh contributes to the formation of different arches and consequently in the development of cartilage and bones of the face during development in Xenopus laevis.